Heterocyclic Aromatic Amines and Risk of Kidney Stones: A Cross-Sectional Study in US Adults - Zhang, Guangyuan; Zou, Xiangyu; Mao, Weipu; Chen, Ming (Frontiers in Public Health, 2022)
Background Heterocyclic aromatic amines (HAAs) are a group of harmful substances produced while cooking meat at high temperatures. This study aimed to investigate the relationship between HAAs and the occurrence of kidney stones. Methods Data on the level of four HAAs, including 2-Amino-9H-pyrido[2,3-b]indole (A-α-C), 1-Methyl-9H-pyrido[3,4-b]indole (Harman), 9H-Pyrido[3,4-b]indole (Norharman), and 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), in the urine from adult participants were extracted from the 2013-2014 NHANES database. Propensity score matching (PSM) was used to balance confounding variables between the stone former and non-stone former groups, and logistic regression analysis was performed to analyze the relationship between HAAs and the occurrence of kidney stones. Results Of the 1,558 eligible participants, a history of kidney stones was self-reported by 140 (9.0%). Compared to non-stone formers, stone formers had higher concentrations of A-α-C, Harman, and Norharman and lower concentrations of PhlP in urine. After adjusting for all other confounding variables, multivariate logistic regression analysis showed that the high-Harman group had a higher risk of kidney stones than the low-Harman group (adjusted odds ratios [aOR]=1.618, 95% confidence interval [CI]: 1.076–2.433, p=0.021). After PSM analysis, Harman concentration remained a risk factor for kidney stones (high-Harman group vs. low-Harman group: aOR=1.951, 95% CI: 1.059–3.596, p=0.032). Conclusion Increased urinary Harman concentrations are associated with an increased risk of kidney stones in the general US population.